Some relations between the sets of f-statistically convergent difference sequences - Asaad, Sarkawt; Colak, Rifat; Altin, Yavuz (Univ Estadual Maringa, Pro-Reitoria Pesquisa Pos-Graduacao, 2023)
In this study we establish the relations between the sets of difference sequences which are statistically convergent in connection with modulus functions.
Keywords: density; modulus function; difference sequence; statistical convergence